Public interest in healthy lifestyle changes before and during the COVID-19 pandemic: Google Trends analysis - Seyma Trabzon; Pelin Ilhan; Havva Sert; Ali Sarıdas (Information Research: An International Electronic Journal)
Introduction. Healthy lifestyle behaviors are accepted as non-pharmacological approaches in the management of diseases. During the pandemic, individuals started to use the internet to get information and protect their health.